1993
DOI: 10.1007/bf00195082
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the contribution of pseudocyclic photophosphorylation to the energy requirement of the mechanism for concentrating inorganic carbon in Chlamydomonas

Abstract: Abstract. Mass-spectrometric measurements of 1602 and 802 were made to compare the rates of light-dependent 02 evolution and uptake by Chlamydomonas reinhardtiiDang. grown in air (0.035% CO2; low-C~ cells) or CO2-enriched air (5% CO2; high-Ci cells) at pH 5.5 and 8.0.While at pH 5.5, no differences were observed in the isotopic Oz-gas exchange of high-and low-Ci cells, at pH 8.0 the rates of true 02 evolution and uptake were considerably higher in low-C i than in high-C~ cells. The enhanced rates of 02 uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
1
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 32 publications
(68 reference statements)
7
29
1
1
Order By: Relevance
“…High pH can reduce algal photosynthetic ability and pigment content, because the dissolved CO 2 in water is limited (Axelsson et al 1999;Olischläger et al 2013). Meanwhile, the depletion of dissolved CO 2 stimulates ROS formation (Sültemeyer et al 1993). Compared to the NaCl stress, Na 2 CO 3 stress induced more ROS production and had more toxic effects on algal photosynthetic pigments and ability, which might be caused by the high pH.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…High pH can reduce algal photosynthetic ability and pigment content, because the dissolved CO 2 in water is limited (Axelsson et al 1999;Olischläger et al 2013). Meanwhile, the depletion of dissolved CO 2 stimulates ROS formation (Sültemeyer et al 1993). Compared to the NaCl stress, Na 2 CO 3 stress induced more ROS production and had more toxic effects on algal photosynthetic pigments and ability, which might be caused by the high pH.…”
Section: mentioning
confidence: 99%
“…It has been reported that high pH reduces algal photosynthetic ability and pigment content, because it limits dissolved CO 2 -concentration in water (Axelsson et al 1999;Olischläger et al 2013). The depletion of dissolved Effects of NaCl and Na2CO3 stresses 1315 CO 2 can stimulate ROS formation, increase antioxidant enzyme activity (Sültemeyer et al 1993) and even induce PCD (Vardi et al 1999). In our previous study, we found that Na 2 CO 3 stress can increase the emission of VOCs from Chlamydomonas reinhardtii (Zuo et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Bicarbonate accumulation in the cytoplasm is thought to have an ATP : HCO K 3 or NADH : CO 2 cost ratio of 1 (but see Ritchie et al 1996). This ATP demand for CCM operation can be supplied directly by thylakoid pathways described in §5 (figure 6), including the pseudocyclic pathway (Mehler; Miller et al 1988;Sü ltemeyer et al 1993). Rubisco levels are also elevated under low CO 2 conditions to overcome slow catalytic rates (Tortell et al 2000), representing an additional resource cost to the cell.…”
Section: Nutrientsmentioning
confidence: 99%
“…Gross Oxygen Evolution and Oxygen Uptake-Gross oxygen evolution and oxygen uptake was measured at 25°C using a system described previously (39). Actinic light was provided by a slide projector (Braun) with heat filter.…”
Section: Sds-page and Westernmentioning
confidence: 99%